Surgical Repair of a Quadricuspid Aortic Valve With Severe Regurgitation Utilizing “Tricuspidization” and Annular Banding: A Case and Technique Details Report - Yu, Yang; Huang, Ruixuan; Ding, Zheng; Shi, Enyi; Gu, Tianxiang (Frontiers in Cardiovascular Medicine, 2022)
The quadricuspid aortic valve (QAV) is a rare congenital disease with a prevalence of 0. 013–0.043% of cardiac cases. Most patients with QAV are treated with aortic valve replacement. A Type B QAV with dilated ascending aorta of 47.9 mm; combined with severe regurgitation is reported here. In this case, considering the patient‘s cusps are flexible and reservable, the aortic root was reconstructed utilizing tricuspidization and annular banding technique, and dilated ascending aorta was replaced at the same time.